2010
DOI: 10.1073/pnas.0906355107
|View full text |Cite
|
Sign up to set email alerts
|

An end-joining repair mechanism in Escherichia coli

Abstract: Bridging broken DNA ends via nonhomologous end-joining (NHEJ) contributes to the evolution and stability of eukaryote genomes. Although some bacteria possess a simplified NHEJ mechanism, the human commensal Escherichia coli is thought to rely exclusively on homology-directed mechanisms to repair DNA double-strand breaks (DSBs). We show here that laboratory and pathogenic E. coli strains possess a distinct end-joining activity that repairs DSBs and generates genome rearrangements. This mechanism, named alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
123
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(144 citation statements)
references
References 36 publications
7
123
0
Order By: Relevance
“…For example, transformation frequencies at different genomic loci of Acinetobacter baylyi, which lacks the NHEJ proteins, were shown to vary up to 10,000-fold (Ray et al 2009). Moreover, Chayot et al (2010) recently showed that DNA acquisition in E. coli can be mediated in vitro by a mechanism that is independent of homologous recombination. E. coli, which lacks the NHEJ pathway, possesses an alternative end-joining mechanism (A-EJ) for DNA double-strand break repair (Chayot et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, transformation frequencies at different genomic loci of Acinetobacter baylyi, which lacks the NHEJ proteins, were shown to vary up to 10,000-fold (Ray et al 2009). Moreover, Chayot et al (2010) recently showed that DNA acquisition in E. coli can be mediated in vitro by a mechanism that is independent of homologous recombination. E. coli, which lacks the NHEJ pathway, possesses an alternative end-joining mechanism (A-EJ) for DNA double-strand break repair (Chayot et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Chayot et al (2010) recently showed that DNA acquisition in E. coli can be mediated in vitro by a mechanism that is independent of homologous recombination. E. coli, which lacks the NHEJ pathway, possesses an alternative end-joining mechanism (A-EJ) for DNA double-strand break repair (Chayot et al 2010). The A-EJ mechanism recruits the RecBCD complex for end-restriction and Ligase A for DNA ligation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some species (e.g., Bacillus subtilis) also possess a rudimentary analog to the eukaryotic nonhomologous end-joining pathway (NHEJ) (34), and a modified version of NHEJ, named alternative end joining (A-EJ), exists in E. coli (35). Recently, genome condensation under stress conditions was suggested as an additional DSB repair mechanism that operates in E. coli (36).…”
Section: Discussionmentioning
confidence: 99%
“…Illegitimate recombination occurring during DNA synthesis can be responsible for local sequence conversion, deletion, or duplication. It can arise during DNA replication (336,337), transposition (91, 338), or gyrase-and topoisomerase I-mediated strand cleavage (339-341); as a consequence of UV or gamma irradiation (342-344); or following the transformation of cells with linear DNA sequences under circumstances where homologous recombination is not possible (345,346). Single-strand annealing following a DNA break can occur after DNA degradation, leading to a local deletion.…”
Section: Mechanisms Of Homologous and Illegitimate Recombinationmentioning
confidence: 99%